Comparative efficacy and safety of bicompartmental versus total knee arthroplasty: a systematic review and update meta-analysis - Rongwei Zhang; Xianyue Shen; Kangyong Yan; Xianzuo Zhang; Chen Zhu (Journal of Orthopaedic Surgery and Research)
Abstract Background This study was aimed at comparing the efficacy and safety of bicompartmental knee arthroplasty (BKA) and total knee arthroplasty (TKA) in treating bicompartmental knee osteoarthritis through a systematic evaluation and meta-analysis. Methods A comprehensive systematic literature search of the Pub Med, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov databases was performed to identify the relevant scientific literature published until 1st March 2024. The eligible studies were evaluated for quality assessment and data extraction, and meta-analysis was performed using Review Manager 4.1 software. Results A total of 1378 studies were identified. Based on strict inclusion criteria, 12 studies were finally included in this meta-analysis. The results of the analysis revealed that BKA yielded better postoperative outcomes than TKA, in terms of Knee Society Score (KSS) Knee Score, Function Score, and range of knee flexion (P = 0.02; P < 0.0001; P = 0.0005, respectively). Intraoperative bleeding in the BKA group was significantly lower than that in the TKA group (P = 0.02), although postoperative complications (P < 0.05) were higher and operative time (P = 0.04) was longer in the BKA group. However, the two groups did not show any significant difference in terms of Oxford knee score and WOMAC pain score (P = 0.53 and P = 0.96, respectively). Discussion Our present results indicate that while BKA affords better improvement in knee function and quality of life in bicompartmental knee osteoarthritis than TKA, it also increases complications and operative time. Therefore, further studies are warranted to confirm these results and assess long-term outcomes and cost-effectiveness. Other Systematic review registration PROSPERO CRD420-24551418.